Systematic Review of Risk Identification and Injury Prevention Strategies in Sports Activities - Ecka Maulana Saputra Maulana; Y. Touvan Juni Samodra; Putra Sastaman (Indonesian Journal of Sport Management, 2025)
Background: Risk management studies are an option to ensure planning runs according to programmatic guidelines for optimal athletic performance development. Training programs and healthy living education contribute significantly to improving athlete fitness and abilities. Facilities and infrastructure are also crucial for enhancing athlete performance. Purpose: This study aims to examine the application of risk management in sports. Achieving high performance requires systematic, measured preparation and management. Methods: This research is a literature review. The WOS database used the keyword "risk management" in sports, resulting in 338 articles. A search restricted to the last five years yielded 152 documents, Then the articles were filtered again because they were deemed not to discuss “risk management”, as many as 134 articles. Further narrowing within “the sports science theme” yielded 31 articles. 27 articles matched the abstract to the theme. Results: The research results explain and demonstrate that risk management in sports places greater emphasis on injury management and prevention. This study states that it is important for teachers, athletes, and the public to learn. Furthermore, sports performance development is related to the physical and psychological performance of athletes, the club's organizational structure, the quality of programmed training, and the support of sports facilities and technology. Conclusion: Achieving optimal sports performance requires a strong bond between injury prevention, structured training programs, and good management support.  Implications and Recommendation: To achieve optimal sports performance, it is necessary to integrate injury prevention, a planned training program and good management support.